2008
DOI: 10.1080/02640410701824099
|View full text |Cite
|
Sign up to set email alerts
|

Centre of pressure sway characteristics during static one-legged stance of athletes from different sports

Abstract: The frequency of one-legged stance and two-legged stance differs considerably among sports. We therefore expect the balance ability of athletes from different sports to vary. This study compared the sway characteristics during a static one-legged stance of soccer players, basketball players, swimmers, and non-athletes. The centre of pressure sway during one-legged stance of ten male participants representing each of the four groups was measured using a stabilometer. Centre of pressure sway was assessed by four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
154
4
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(177 citation statements)
references
References 17 publications
14
154
4
5
Order By: Relevance
“…players who do not perform balance training daily, and demonstrated the probability of postural stability deficits in FAI individuals. However, the findings from this study are insufficient to conclude whether individuals with FAI have postural stability deficits; sample bias may have been incurred because of the small number of participants (22) who were recruited from one university soccer team. Therefore, a study with adequate power calculations and a long-term follow-up study would be required to determine the presence of postural stability deficits in individuals with FAI.…”
Section: Conflict Of Interestsmentioning
confidence: 77%
See 2 more Smart Citations
“…players who do not perform balance training daily, and demonstrated the probability of postural stability deficits in FAI individuals. However, the findings from this study are insufficient to conclude whether individuals with FAI have postural stability deficits; sample bias may have been incurred because of the small number of participants (22) who were recruited from one university soccer team. Therefore, a study with adequate power calculations and a long-term follow-up study would be required to determine the presence of postural stability deficits in individuals with FAI.…”
Section: Conflict Of Interestsmentioning
confidence: 77%
“…The study investigated the fatigue effects for sensorimotor control in FAI individuals recruited from various sports, such as basketball and soccer. However, Matsuda et al 22) reported that balance ability to a stable one-legged stance in soccer players was higher than that in the basketball players. The difference in balance ability may influence the result of this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balance performance can be developed through resistance, flexibility, aerobic and anaerobic training (Judge et al, 1993;Messier et al, 2000;Shintaku et al, 2005). Football players use their one leg as support leg when kicking a ball and in possession of the ball (Adlerton et al, 2003;Kellis et al, 2001) and have better one-legged stance stability (Matsuda et al, 2008). Hence, we expect that sprint, acceleration, anaerobic run, vertical or horizontal jump may be related with balance performance in football players.…”
Section: Introductionmentioning
confidence: 99%
“…Static balance has been assessed by measuring the center sway of body gravity while standing [15,16,17]. A Gravicorder G5500 (Anima, Japan) was used to measure foot pressure in this study.…”
Section: Static Balancementioning
confidence: 99%